2017
DOI: 10.18787/jr.2017.24.1.14
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics of Lacrimal Sac Tumors: Report of Ten Cases

Abstract: Background and Objectives:To review our experience with lacrimal sac tumors in an effort to identify features, to evaluate the results of various methods of management, and to compare our data with previous studies. Methods: We reviewed the medical records of all patients with lacrimal sac tumors who were managed in our institution between January 1990 and December 2015. The pre-operative clinical data, imaging, operation notes, and follow-up records were reviewed for each patient. Results: The study group con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Both patients were under observation at the time of the report. Kang et al [28] have reported ten cases of LSTs. Six patients had a history of DCR for dacryostenosis, and the average number of DCR was 3.5.…”
Section: Discussionmentioning
confidence: 99%
“…Both patients were under observation at the time of the report. Kang et al [28] have reported ten cases of LSTs. Six patients had a history of DCR for dacryostenosis, and the average number of DCR was 3.5.…”
Section: Discussionmentioning
confidence: 99%
“…6,20 Recurrence and mortality rates for lacrimal sac tumors vary from case to case. 3,4,[6][7][8][9][10]16,18,20 In the present study the patient did not receive any postoperative adjuvant treatment and no recurrence was revealed during 38 months of follow-up.…”
Section: Discussionmentioning
confidence: 53%
“…Recurrence and mortality rates for lacrimal sac tumors vary from case to case. 3,4,[6][7][8][9][10]16,18,20 In the present study, the patient did not receive any postoperative adjuvant treatment and no recurrence was revealed during 38 months of follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Wide surgical en bloc resection of lacrimal sac tumors with medial maxillectomy or total maxillectomy is favored with good success rates for local disease control 7,9 . Orbit exenteration, resection of the paranasal sinuses, or lymph node dissection is performed in certain advanced cases 8,18 . Song et al 10 reported that the outcomes of comprehensive treatment were quite encouraging, and the 5‐year overall survival rate and 5‐year progression‐free survival rate were 87.6% ± 4.8% and 76.3% ± 6.4%, respectively.…”
Section: Discussionmentioning
confidence: 99%